THE CORRELATION OF ARTISTIC EXPERIENCE IN ENGLISH SPEAKING SELF-CONFIDENCE AMONG PERFORMING ART STUDENTS - Agustin Anggraeni; Rilis Anggraeni; Ahlan Wijaya (Universitas Duta Bangsa Surakarta, 2026)
This study aims to explore the role of artistic experience in shaping the English-speaking self-confidence of performing arts students. The research is based on the assumption that artistic experiences—such as performing on stage, singing, dancing, or acting—can foster self-expression that influences confidence in using English. In a global context, English-speaking ability is essential for performing arts students to express their work internationally. However, English learning approaches in art education settings rarely consider artistic experience as a psychological asset. Studies conducted previously related to self-confidence and English ability focus on either intervention of particular media or specifically empirical art experience only. This research brings novelty through the exploration of artistic experience in relation to English speaking confidence. The authors employed a mixed-method design with a sequential explanatory approach, beginning with quantitative data collection through a Likert-scale questionnaire to measure the level of English-speaking confidence, followed by qualitative data collection through semi-open questionnaires and interviews to explore artistic experiences in depth. The participants consisted of 33 purposively selected students from the Faculty of Performing Arts who had completed at least three semesters and had prior experience using English in various contexts. The findings indicate that the English-speaking confidence level of performing arts students is at a moderate level. Furthermore, the results of the Spearman correlation test show that students’ artistic experiences do not play a significant role in shaping their English-speaking confidence. This is due to the presence of more dominant factors affecting self-confidence, such as opportunities to practice English, vocabulary mastery, and other linguistic factors.